Sensing China: modern transformations of sensory culture - Wu, Shengqing; Huang, Xuelei (Routledge, 2023)
"This book presents the first collection of studies of the senses and sensory experiences in China, filling a gap in sensory research while offering new approaches to Chinese Studies. Bringing together twelve chapters by literary scholars and historians, this book critically interrogates the deeply rooted meanings that the senses have coded in Chinese culture and society. Built on an exploration of the sensorial in early Chinese thought and late imperial literature, this book reveals the sensory manifestations of societal change and cultural transformation in China from the nineteenth century to the present day. It features in depth examinations of a variety of concepts, representations, and practices, including aural and visual paradigms in ancient Chinese texts; odours in Ming Qing literature and Republican Shanghai; the tactility of kissing and the sonic culture of community singing in the Republican era; the socialist sensorium in art, propaganda, memory, and embodied experiences; as well as contemporary-era multisensory cultural practices. Engaging with the exciting 'sensory turn', this original work makes a unique contribution to the world history of the senses, and will be a valuable resource to scholars and students of Chinese Literature, History, Cultural Studies, and Media"--
Includes bibliographical references and index
Keywords: Sozialer Wandel; Kulturwandel; Wandel; Sinne; Empfindung; China